Pengaruh Metode Mengajar Inquiry dan Minat Membaca Terhadap Kemampuan Menulis Cerita Pendek Siswa Kelas XI SMA Negeri Sekota Samarinda - Elyana, Kukuh; Slamet, St. Y.; Suwandi, Sarwiji (Universitas Mulawarman, 2019)
This research aims to find out the difference between teaching inquiry methods and teaching methods of two stay two strays; differences of students who have high and low interest in reading; as well as the interaction between teaching methods and reading interest in the ability to write short stories. The research method is a 2x2 factorial design experiment research, with the research population of all students of Samarinda City State High School. Research data is obtained through tests of writing short stories and reading interest questionnaires. Based on the analysis of data obtained results, there is a difference between students with teaching method inquiry and two stay two stray from the statistical results Fh = 21.57 > Ft = 4.01; there is a difference in ability between students interested in high reading and low reading interest with statistical results Fh = 15.12 > Ft = 4.01; There is an interaction between teaching methods and reading interest in short story writing skills with statistical results Fh = 6.41 > Ft = 4.01. The conclusion of this study is: the method of teaching inquiry is better than two stay two strays; high reading interest is better than low reading interest; there is also an interaction between teaching inquiry methods and reading interest in short story writing skills.